Taxonomy Of Successful Digital Transformation Adoption Of Software As A Service Cloud Accounting Services For SMES - Endar Pradesa; Ratih Eka Sakti; Metha Aditya Putri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Information technology such as software as a service can be used to improve business transformation, accuracy and efficiency of business information which can realize the competitiveness of SMEs. There are several advantages and conveniences offered by technological transformation using software as a service to SMEs, namely payments are paid in stages or paid according to usage. This can save time, reduce operational costs, reduce space requirements, make it easy to access, facilitate the data analysis process. After several advantages have been described, the figure for the use of information systems in the form of Software as a Service is still quite small in Indonesia. This research uses the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The aim of this research is to test and prove that the variables Individual Factors, Social Factors, Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavior Intention to Use influence each other. Quantitative research methods are a type of research that is systematic, planned and clearly structured from the beginning until the creation of the research design. The aim of quantitative research is to develop and use mathematical models, theories and hypotheses related to phenomena. The results of this research show that all variables Individual Factors, Social Factors, Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavior Intention to Use have a positive influence on each other.